2022
DOI: 10.1097/icl.0000000000000952
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antiviral Resistance on Herpetic Keratitis

Abstract: Herpes simplex keratitis resistance to antiviral treatment presents a growing concern. The herpes simplex virus has many different mechanisms of resistance to antiviral treatment, which have been well described. Resistance to acyclovir occurs because of mutations in the viral thymidylate kinase and DNA polymerase that decrease this enzyme's affinity for its substrate. This article discusses factors that explain the prevalence of this resistance, the ability for recurrences in immunocompromised populations, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Acyclovir is the most common drug used in the management of HSK[ 169 ], although eyedrops are now being proposed[ 170 ]. Resistance to acyclovir occurs due to extended use[ 171 ], and mutation in the viral thymidylate kinase and DNA polymerase which decreases enzyme affinity for its substrate[ 172 - 174 ]. Topical cyclosporine drops and prednisolone acetate drops are statistically similar in potency for stemming inflammation and preventing scar development[ 175 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%
“…Acyclovir is the most common drug used in the management of HSK[ 169 ], although eyedrops are now being proposed[ 170 ]. Resistance to acyclovir occurs due to extended use[ 171 ], and mutation in the viral thymidylate kinase and DNA polymerase which decreases enzyme affinity for its substrate[ 172 - 174 ]. Topical cyclosporine drops and prednisolone acetate drops are statistically similar in potency for stemming inflammation and preventing scar development[ 175 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%
“…9,16, 17 Although current antivirals are still viable treatments for active herpetic diseases such as keratitis, controlling recurrence and the virus in the latent phase remains a challenge due to a virus in its latent state being resistant to all antiviral drugs. 14, [16][17][18] Vaccines targeting this viral group have not yet been developed, which increases the need for effective therapies that not only safely treat active herpesvirus infection, but also aim to prevent latent infection. Understanding the pathogenesis and virulence characteristics of herpesviruses can lead to new therapeutic targets to prevent the virus from entering, spreading and replicating.…”
Section: No Outbreaksmentioning
confidence: 99%
“…Efforts to address these challenges include developing innovative therapies targeting acyclovir-resistant herpes simplex keratitis. 272 Famciclovir is an alternative treatment option for genital herpes. 273,274 As substantiated by research findings, zinc has demonstrated the capacity to impede the viral life cycle of HSV.…”
Section: Current Antiviral Therapies For Hsv Infectionmentioning
confidence: 99%